2006
DOI: 10.1593/neo.05850
|View full text |Cite
|
Sign up to set email alerts
|

Cardenolide-Induced Lysosomal Membrane Permeabilization Demonstrates Therapeutic Benefits in Experimental Human Non-Small Cell Lung Cancers

Abstract: Non-small cell lung cancers (NSCLCs) are the leading cause of cancer deaths in most developed countries. Targeting heat shock protein 70 (Hsp70) expression and function, together with the induction of lysosomal membrane permeabilization (LMP), could overcome the multiple anti-cell death mechanisms evidenced in NSCLCs that are responsible for the failure of currently used chemotherapeutic drugs. Because cardenolides bind to the sodium pump, they affect multiple signaling pathways and thus have a number of marke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
120
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 46 publications
6
120
0
1
Order By: Relevance
“…29,30) Recent studies have found that decreasing a1 subunit expression using specific siRNA markedly altered A549 NSCLC cell and U373-MG GBM cell morphology, impaired proliferation and migration via an intracellular adenosine triphosphate (ATP) decrease-mediated disorganization of the actin cytoskeleton and cytotoxic proautophagic effects, or by increasing the intracellular Ca 2ϩ , ROS concentration. 10,11) In our study, we found ouabain could induce HepG2 cell apoptosis by increasing the intracellular Ca . 32) For intracellular free Ca 2ϩ to be a sort of second messenger, it is essential to maintain the ion balance and signal transduction in physiological concentrations, although a higher concentration of intracellular free Ca 2ϩ could participate in the double strand breaks of DNA in reducing cell apoptosis, including activating Ca 2ϩ /Mg 2ϩ dependent nucleate endonuclease, inhibiting topoisomerase I, II activity, and inducing changes in chromosomal structure.…”
Section: Effect Of Ouabain and Sirna On Hepg2 Cell Apoptosissupporting
confidence: 48%
See 1 more Smart Citation
“…29,30) Recent studies have found that decreasing a1 subunit expression using specific siRNA markedly altered A549 NSCLC cell and U373-MG GBM cell morphology, impaired proliferation and migration via an intracellular adenosine triphosphate (ATP) decrease-mediated disorganization of the actin cytoskeleton and cytotoxic proautophagic effects, or by increasing the intracellular Ca 2ϩ , ROS concentration. 10,11) In our study, we found ouabain could induce HepG2 cell apoptosis by increasing the intracellular Ca . 32) For intracellular free Ca 2ϩ to be a sort of second messenger, it is essential to maintain the ion balance and signal transduction in physiological concentrations, although a higher concentration of intracellular free Ca 2ϩ could participate in the double strand breaks of DNA in reducing cell apoptosis, including activating Ca 2ϩ /Mg 2ϩ dependent nucleate endonuclease, inhibiting topoisomerase I, II activity, and inducing changes in chromosomal structure.…”
Section: Effect Of Ouabain and Sirna On Hepg2 Cell Apoptosissupporting
confidence: 48%
“…[4][5][6][7][8][9] The main reason was the expression of Na ϩ /K ϩ -ATPase in cancer cells was higher than that in normal cells, and provided more binding sites for CSs. Previous research has shown the Na ϩ /K ϩ -ATPase a1 subunit was highly expressed in malignant cells, including human prostate cancer PC-3, DU-145 cells, human non-small cell lung cancer (NSCLC) A549 cells, 10) glioblastomas Hs683, U373-MG, U87-MG, T98G cells, 11) and breast cancer MCF-7 cells. 12) Mijatovic found that cell invasion and proliferation were significantly reduced after knockdown of the Na ϩ /K ϩ -ATPase a1 subunit expression in NSCLC (A549) cells.…”
mentioning
confidence: 99%
“…In conclusion, the data from the present study are part of a larger story revealing that several natural compounds, including cardiotonic steroids (17,26,27) and Kahalalide F (37,38), have been recently identified as having the ability to kill apoptosis-resistant cancer cells through sustained proautophagic and/or lysosomal membrane permeabilization processes. Thus, it seems that the in vitro growth inhibitory activities displayed by compounds 1-4 in the present study, which are similar to those displayed by temozolomide, a compound used to combat cancers associated with dismal prognoses, and similar for 'apoptosis-resistant' and 'apoptosissensitive' cancer cells, are quite encouraging to enter into hemisyntheses intended to obtain alternethanoxin derivatives with higher activities against cancer cells that display intrinsic resistance to pro-apoptotic stimuli.…”
Section: Resultsmentioning
confidence: 63%
“…The present study shows that ISP is able to induce apoptoticrelated cell death in human GBM cells (the U373 model) that display resistance to various pro-apoptotic stimuli (17,18), while ISP is not able to induce apoptosis in human NSCLC cells (the A549 model) that are also displaying a certain level of resistance to various pro-apoptotic stimuli (13,19). We have previously deciphered, at least partly, how ISP induces apoptosis in the human HCT-116 colon cancer cells (9), which displays sensitivity to pro-apoptotic stimuli (24,25).…”
Section: Discussionmentioning
confidence: 87%
“…Apoptosis and necrosis were determined using flow cytometry analyses of Annexin V/propidium iodide double staining, as detailed elsewhere (15,18,19,23). Experiments were performed in triplicate.…”
Section: In Vitro Computer-assisted Phase-contrast Microscopy Analysementioning
confidence: 99%